2015
DOI: 10.1007/s00429-015-1110-z
|View full text |Cite
|
Sign up to set email alerts
|

Callosal anatomical and effective connectivity between primary motor cortices predicts visually cued bimanual temporal coordination performance

Abstract: Default in-phase coupling of hand movements needs to be suppressed when temporal coordination is required for out-of-phase bimanual movements. There is lack of knowledge on how the brain overrides these default in-phase movements to enable a required interval of activity between hands. We used a visually cued bimanual temporal coordination (vc-BTC) paradigm with a constant rhythmical time base of 1 s, to test the accuracy of in-phase and out-of-phase (0.1, 0.2,…,0.9) finger tapping. We hypothesized that (1) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 82 publications
(133 reference statements)
2
9
0
Order By: Relevance
“… Voineskos et al (2010) found an inverse correlation between ISP and functional anisotropy of callosal fibers, highlighting a possible inhibitory role for callosal fibers with suprathreshold stimulation. In our data, we could not find larger ISPs in the MS group, possibly due to impaired callosal inhibitory mechanisms, as previously observed in MS patients at an early stage ( Wahl et al, 2011 , 2016 ).…”
Section: Discussionsupporting
confidence: 76%
“… Voineskos et al (2010) found an inverse correlation between ISP and functional anisotropy of callosal fibers, highlighting a possible inhibitory role for callosal fibers with suprathreshold stimulation. In our data, we could not find larger ISPs in the MS group, possibly due to impaired callosal inhibitory mechanisms, as previously observed in MS patients at an early stage ( Wahl et al, 2011 , 2016 ).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies showed a positive correlation between microstructural integrity of the corpus callosum (FA-based) and strength of interhemispheric inhibition in adults [100,112] and in the course of motor development [113]. In particular, it has been shown that increased FA predicts interhemispheric inhibitory capacity [69].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the bias inherent in each technique before drawing extensive conclusions on the physiology of neuronal networks, it may therefore be advisable to integrate two or more techniques -by carefully considering what they really reflect and do not reflect in brain function-and attempt to arrive at interpretations that hold true independent of the network-probing technique used. Mutually informative data have been derived from combinations of EEG and fMRI (Bönstrup et al, 2016), MEG and fMRI (Ahlfors et al, 1999), TMS and fMRI (Volz et al, 2014) but also from TMS and structural MRI metrics like DTI (Wahl et al, 2007(Wahl et al, , 2016 and many others (Nguyen et al, 2014;Klamer et al, 2015;Petro et al, 2017). With respect to modeling of neuronal networks, e.g., coupled oscillator models, informing functional connectivity matrices derived from EEG recordings integrated by structural Fig.…”
Section: The Added Value Of Multimodal Connectivity Analysesmentioning
confidence: 99%